(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Tien Giang is located in the area of Mekong River, the gateway to the southwestern region, blessed with many beautiful landscapes and valuable historical and cultural relics. Tien Giang is currently an attractive area for marine tourism, ecotourism, cultural tourism, and spiritual tourism. Over the past years, Tien Giang tourism has had a strong development, making a positive contribution to the province’s economy and society. However, in order for Tien Giang tourism to develop sustainably, one of the top concerns today is environmental protection. Environment plays a decisive role in the orientation of sustainable tourism development. The article analyses the results of recent research and results of the paper confirms that we need to have some practical solutions and the paper also mentions the important role of functional industries, they need to implement many synchronous solutions to protect the environment, contributing to creating landscape, improve regional climate and work towards a green and sustainable tourism. In particular, the propaganda and education measures to raise people’s awareness of environmental protection need more attention.